The Maqasid al-Shari’ah and the Protection of Family Economics in Islamic Law: A Reflection on Surah al-Baqarah 2:188 - Saidu Ado; Mohammad Abdel Salama; Abdallah Saleh Abdallah (QURU’: Journal of Family Law and Culture, 2025)
Islam is a comprehensive way of life and a dynamic religion that encourages its followers to adhere to its teachings in addressing new and emerging issues through the application of Maqasid al-Shari’ah. This study explores the role of Maqasid al-Shari’ah in safeguarding family economics within Islamic law, with particular reference to Surah al-Baqarah verse 2:188, which provides divine guidance prohibiting unjust appropriation of others’ wealth. The family unit is the fundamental pillar of society, and its economic stability is crucial for social welfare and justice. However, economic challenges such as unfair wealth distribution, fraud, and mismanagement threaten family wellbeing. The objective of this paper is to acknowledge the principle of Maqasid al-Shari’ah known as the protection of wealth (hifz al-mal) as a sustainable solution to economic crises faced by families and society at large. The research addresses how Maqasid al-Shari’ah can be effectively applied within Islamic jurisprudence to preserve family economic rights and prevent economic harm, thus promoting economic justice and social harmony. Using a combined research methodology that involves both qualitative doctrinal analysis of primary Islamic legal texts (including the Qur’an and classical jurisprudence) and empirical data from fieldwork, this study also employs thematic analysis to identify key principles relevant to economic protection in families. The findings suggest that implementing the objectives of Maqasid al-Shari’ah, particularly hifz al-mal, offers practical and ethical solutions to contemporary economic challenges. By integrating these principles into daily life and governance, economic crises can be mitigated while strengthening social justice and preserving family welfare. Surah al-Baqarah 2:188 reinforces this framework by emphasizing the prohibition of corruption and wrongful seizure of wealth. Ultimately, this study concludes that Maqasid al-Shari’ah provides a holistic and dynamic approach for addressing economic issues within the family and broader society in accordance with Islamic law.